Fostering Agriculture Under the Industrializing State:The Caja de Crédito Agrario and Agricultural Credit in Post-Depression Chile, 1926-53 [Fomentando la Agricultura en el Estado Industrializador: La Caja de Crédito Agrario y el Crédito Agrícola en el Chile Postdepresión, 1926-53] - Robles-Ortiz, C; Gonzalez-Correa, I (Universidad de Murcia, 2022)
Tvelopment inghis paperits officialanalyzes of the annual agricultural thereports,role ofreports credit the Caja market fromdetheCrédito in Superintendency post-depression Agrario (CCA) Chile. of Banks,in Employ- theanddeChile’s StatisticalYearbooks, we constructed the first series of CCA’s credit operations, and established trends in the number, the average amount, and the social, geographic, and specific economic activity distribution of all loans. From 1927 to 1952, CCA loans represented 11.5% of all commercial bank loans, and in the latter year the CCA lent more money to agriculture than any other bank.The CCA became Chile’s largest agricultural bank, right before being merged with other institutions to create the State Bank of Chile. The CCA’s credit was decentralized:its operations evolved towards a fairly balanced distribution of loans among Chile’s main agricultural provinces.This was a micro-credit institution that allocated the vast majority of its loans to small farmers, who otherwise would not have access to formal credit.The CCA was a public policy tool for helping small farmers produce food for domestic consumption. Contrary to conventional views, in Chile the industrialization-promoting state did also foster agricultural growth through CCA public credit. © 2022 The Author(s)